Enhancing cell seeding and osteogenesis of MSCs on 3D printed scaffolds through injectable BMP2 immobilized ECM-Mimetic gel. Issue 7 (July 2019) - Fahimipour, Farahnaz; Dashtimoghadam, Erfan; Mahdi Hasani-Sadrabadi, Mohammad; Vargas, Jessica; Vashaee, Daryoosh; Lobner, Douglas C.; Jafarzadeh Kashi, Tahereh S.; Ghasemzadeh, Behnam; Tayebi, Lobat
Graphical abstract: Abstract: Objective: Design of bioactive scaffolds with osteogenic capacity is a central challenge in cell-based patient-specific bone tissue engineering. Efficient and spatially uniform seeding of (stem) cells onto such constructs is vital to attain functional tissues. Herein we developed heparin functionalized collagen gels supported by 3D printed bioceramic scaffolds, as bone extracellular matrix (ECM)-mimetic matrices. These matrices were designed to enhance cell seeding efficiency of mesenchymal stem cells (MSCs) as well as improve their osteogenic differentiation through immobilized bone morphogenic protein 2 (BMP2) to be used for personalized bone regeneration. Methods: A 3D gel based on heparin-conjugated collagen matrix capable of immobilizing recombinant human bone morphogenic protein 2 (BMP2) was synthesized. Isolated dental pulp Mesenchymal stem cells (MSCs) were then encapsulated into the bone ECM microenvironment to efficiently and uniformly seed a bioactive ceramic-based scaffold fabricated using additive manufacturing technique. The designed 3D cell-laden constructs were comprehensively investigated trough in vitro assays and in vivo study. Results: In-depth rheological characterizations of heparin-conjugated collagen gel revealed that elasticity of the matrix is significantly improved compared with freely incorporated heparin. Investigation of the MSCs laden collagen-heparin hydrogels revealed their capability to provide spatiotemporal bioavailability of BMP2 while suppressing the matrix contraction over time. The in vivo histology and real-time polymerase chain reaction (qPCR) analysis showed that the designed construct supported the osteogenic differentiation of MSCs and induced the ectopic bone formation in rat model. Significance: The presented hybrid constructs combine bone ECM chemical cues with mechanical function providing an ideal 3D microenvironment for patient-specific bone tissue engineering and cell therapy applications. The implemented methodology in design of ECM-mimetic 3D matrix capable of immobilizing BMP2 to improve seeding efficiency of customized scaffolds can be exploited for other bioactive molecules.